2013
DOI: 10.3109/02699052.2013.848378
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of how individuals reconstruct their sense of self following acquired brain injury in comparison with spinal cord injury

Abstract: Findings are discussed in relation to proposed models of self-reconstruction post-injury to the nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…The operationalizations of these Psychological research on SCI includes studies on social support, [22][23][24][25] sense of self, 18,26,27 purpose in life, 15,18,26 spiritual coping 28 and spirituality. 4,16,29,30 In studies on social support the importance of supportive relationships is widely recognized.…”
Section: Discussionmentioning
confidence: 99%
“…The operationalizations of these Psychological research on SCI includes studies on social support, [22][23][24][25] sense of self, 18,26,27 purpose in life, 15,18,26 spiritual coping 28 and spirituality. 4,16,29,30 In studies on social support the importance of supportive relationships is widely recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Implications of sudden onset life‐changing injury and subsequent disability have been recently reported by Lennon et al . (), with ‘a feeling of lost autonomy’ identified by people with ABI due to the effects of reduced cognitive functioning on each person's decision‐making ability (Lennon et al . , p. 36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that actual growth is represented by a combination of positive and negative effects of trauma, whilst growth that is reported in the absence of negative effects will potentially lead to maladjustment stemming from ineffective coping strategies such as denial or deliberate attempts not to think of the trauma. [12] It could be argued that positive and negative consequences are interwoven and necessary for growth to take place, [13] and it would therefore be informative to measure both positive and negative dimensions of change following trauma, for example with the Psychological Well-BeingPost-Traumatic Changes Questionnaire, [14] which asks respondents to state whether a given positive attribute applies more, less, or the same as before the traumatic event. The PTGI was used in the present study because it is the most commonly used measure in the existing literature on PTG following ABI, but future research would benefit from employing alternative measures that capture broader post-traumatic experiences, including those specific to medical trauma.…”
Section: Other Commentsmentioning
confidence: 99%